Antihypertensive potential of Brassica rapa leaves: An in vitro and in silico approach - Abid, Rohma; Islam, Muhammad; Saeed, Hamid; Ahmad, Abrar; Imtiaz, Fariha; Yasmeen, Anam; Rathore, Hassaan Anwer (Frontiers in Pharmacology, 2022)
Aim: Plants contain many essential constituents and their optimization can result into the discovery of new medicines. One such plant is Brassica rapa, commonly used as a vegetable to fulfill daily food requirement worldwide. This study intends to screen the phytochemicals, antihypertensive potential, GC-MS and in silico analysis of the leaves of Brassica rapa. Methods: Powdered leaves were subjected to proximate analysis followed by estimation of primary metabolites. Extracts were obtained by hot and cold extraction and investigated for secondary metabolites. All crude extracts were screened for their antihypertensive potential using angiotensin converting enzyme (ACE) inhibition assay. GC-MS analysis was carried out to standardize the extract and antihypertensive metabolite was confirmed using in silico approach. Results: Physicochemical evaluation resulted in moisture content (9.10%±0.1), total ash value (18.10% ± 0.6) and extractive values (water 9.46% ± 0.5 and alcohol soluble 4.99% ± 0.1) while phytochemical investigation revealed primary metabolites (total proteins 11.90 mg/g ± 0.9; total fats 3.48 mg/g ± 0.5; and total carbohydrates 57.45 mg/g ± 1.2). Methanol extract showed highest amount of secondary metabolites including polyphenols 93.63 mg/g ± 0.6; flavonoids 259.13 mg/g ± 0.6; and polysaccharides 56.63 mg/g ± 1.4, while water extract (70 mg/g ± 2) was rich in glycosaponins. Methanol extract showed the highest antihypertensive potential by inhibiting ACE (79.39%) amongst all extracts, compared to the standard drug captopril, which inhibited 85.81%. Standardization of methanol extract via GC-MS analysis revealed potent phyto constituents and molecular docking study confirmed that oleic acid is the main antihypertensive metabolite. Conclusion: We conclude that leaves of Brassica rapa can successfully lower hypertension by inhibiting ACE, however; in vivo investigations are required to confirm this antihypertensive activity.